ANALYSIS OF THE EFFECTIVENESS OF SERVICES ON MOTOR VEHICLE TAX COLLECTION IN THE REGIONAL REVENUE MANAGEMENT UNIT OF THE SOUTH MEDAN ONE-STOP INTEGRATED ADMINISTRATION SYSTEM (SAMSAT) - Laila Jamilah Lubis; Suwardi Lubis; Erlina Erlina (LPPM Institut Pendidikan Nusantara Global, 2023)
This study discusses the service of motor vehicle tax collection and its relation to public services in the Regional Revenue Management Unit (UPPD) of the South Medan One-Stop Integrated Administration System (SAMSAT). Public service is a form of service provided by the bureaucracy or the government to the community. Implementation of public services is intended to meet the needs in accordance with the wishes and expectations of the community. The objectives of this study were: (1) to analyze the effectiveness of the service for collecting PKB at UPPD SAMSAT South Medan, and (2) to analyze the inhibiting factors for PKB services at UPPD SAMSAT South Medan. The research method used is a quantitative approach. As for the results in this study, the output of the Chi square test analysis is known to be the Asymp value. Sig. (2-sided) on the pearson chi square test is 0.000 that H0 is rejected and Ha is accepted. Thus it can be interpreted that there is a relationship between Service Effectiveness and Motor Vehicle Tax Collection in the South Medan SAMSAT UUPD. And the relationship between service effectiveness and motor vehicle tax collection at UPPD SAMSAT South Medan through Spearman's analysis. Where the results obtained are that there is a relationship between variables as much as 0.242, 0.086, and -0.68. Where these three results show that there is a fairly strong relationship between X and Y variables.